2018
DOI: 10.1021/acs.joc.8b02480
|View full text |Cite
|
Sign up to set email alerts
|

Influences of Phenyl Rings on NHC Ligands with Bicyclic Architectures

Abstract: In addition to phosphanes, olefins, amines, and amides, over the past two decades N-heterocyclic carbene (NHC) has emerged as a useful alternative ligand. Based on a number of derivatization studies on NHC ligands, imidazol-2-ylidene and imidazolin-2-ylidene became the standard heterocyclic form, and bulky substituents have commonly been introduced on the nitrogen(s) adjacent to carbenic carbons. Our group previously developed NHCs equipped with noncarbenic carbons with a bicyclic architecture that gives them … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(20 citation statements)
references
References 49 publications
1
19
0
Order By: Relevance
“…These silver complexes were stable under air on a bench in the solid state and isolated as colorless crystalline solids. Because we previously analyzed DHASIMeAgCl 4 and BCPSIMeAgCl 8 complexes using XRD studies, we attempted XRD studies with these novel silver complexes to observe the influences of N -substituents. Single crystals of these complexes were obtained via the slow diffusion of n -hexane in CH 2 Cl 2 solutions of BCPSI i PrAgCl 13 or BCPSICyAgCl 14 at ambient temperature, and the ORTEP diagrams appear in Figure a,b.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These silver complexes were stable under air on a bench in the solid state and isolated as colorless crystalline solids. Because we previously analyzed DHASIMeAgCl 4 and BCPSIMeAgCl 8 complexes using XRD studies, we attempted XRD studies with these novel silver complexes to observe the influences of N -substituents. Single crystals of these complexes were obtained via the slow diffusion of n -hexane in CH 2 Cl 2 solutions of BCPSI i PrAgCl 13 or BCPSICyAgCl 14 at ambient temperature, and the ORTEP diagrams appear in Figure a,b.…”
Section: Resultsmentioning
confidence: 99%
“…Our group has developed original NHCs that possess bicyclic architectures on the noncarbenic carbons of imidazolidin-2-ylidene, which we refer to as DHASI or as BCPSI (Figure b). These two core examples of NHC architecture showed good shielding effects when we used them as ligands to form their silver, , copper, and nickel complexes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These observed signals approximated those previously reported for other saturated NHOs (Figure S12 in the Supporting Information), indicating that an aromatic ring probably does not exert a strong anisotropic effect on the olefin. In our previous studies, stable metal complexes were obtained even with N,N ′-dimethyl NHC ligands (DHASIMe or BCPSIMe); however, an N , N ′-dimethyl-saturated NHO was not successfully isolated, which was probably due to instability under the reaction conditions. On the contrary, we were able to isolate the N,N ′-diisopropyl-saturated NHO 3 .…”
Section: Resultsmentioning
confidence: 98%
“…Our group previously synthesized NHC ligands equipped with bicyclic architectures on the noncarbenic carbons, which we referred to as DHASI and BCPSI (Figure a). During the course of our study to develop useful transition metal catalysts using these NHCs, we found that the aromatic rings facing the bound metals were effectively stabilized C–M bonds of the NHC–metal complexes, which made for easier handling and resulted in good catalyst performance during reactions catalyzed by either copper or nickel .…”
Section: Resultsmentioning
confidence: 99%